2006
DOI: 10.1124/mol.105.017756
|View full text |Cite
|
Sign up to set email alerts
|

Increased Divalent Metal Transporter 1 Expression Might Be Associated with the Neurotoxicity of l-DOPA

Abstract: Based on the available data, we speculated that changes in brain iron metabolism induced by L-DOPA might be associated with the neurotoxicity of L-DOPA. To investigate this possibility, the effects of L-DOPA on the expression of iron influx proteins [transferrin receptor (TfR) and divalent metal transporter 1 (DMT1)], iron efflux protein (ferroportin 1), and iron uptake in C6 glioma cells were determined in this study using Northern blot and Western blot analysis and the calcein method. The findings showed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 42 publications
1
24
0
Order By: Relevance
“…A pathological study of postmortem brain tissue showed that the levels of iron storage protein ferritin were significantly lower in several brain regions of PD patients treated with L-DOPA than those in the age-matched control patients [9]. In a recent study, we demonstrated that L-DOPA induces a significant increase in the expression of divalent metal transporter 1 without iron-response element (DMT1−IRE), but not divalent metal transporter 1 with iron-response element (DMT1+IRE), TfR1 or Fpn1, and a remarkable increase in ferrous uptake in cells [10].…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…A pathological study of postmortem brain tissue showed that the levels of iron storage protein ferritin were significantly lower in several brain regions of PD patients treated with L-DOPA than those in the age-matched control patients [9]. In a recent study, we demonstrated that L-DOPA induces a significant increase in the expression of divalent metal transporter 1 without iron-response element (DMT1−IRE), but not divalent metal transporter 1 with iron-response element (DMT1+IRE), TfR1 or Fpn1, and a remarkable increase in ferrous uptake in cells [10].…”
Section: Introductionmentioning
confidence: 82%
“…Based on our recent findings [10], together with the potential role of DMT1−IRE in neuronal iron uptake [10], [22] and the well-known function of iron in the generation of reactive oxygen species, we hypothesized that the upregulation of DMT1−IRE might play a critical role in the development of L-DOPA neurotoxicity. In the present study, efforts were made to test this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports on the role of divalent metal transporter 1 (DMT1), ceruloplasmin (CP), hephaestin (HP), and ferroportin1 (Fpn1) in brain iron transport represent important advances in our understanding of the physiology and pathophysiology of brain iron metabolism. A recent study reported that the treatment of C6 glioma cells with different concentrations of l -DOPA significantly increased the expression of DMT1 (-IRE) mRNA and protein, and enhanced uptake of ferrous iron [6]. These findings suggest that increased DMT1 expression might be associated with the neurotoxicity of l -DOPA.…”
Section: Introductionmentioning
confidence: 99%
“…Iron levels are tightly controlled in the brain and chronically elevated or reduced iron levels have toxic effects [19]. Elevated neuronal iron levels play a role in the neurodegenerative mechanisms that underlie Alzheimer's and Parkinson's disease [8,21] very likely by producing toxic amounts of free radicals [20,26,27]. It is feasible that a lack of control of iron levels in the brain is linked to disturbed FPN1 or Hepc expression.…”
Section: Discussionmentioning
confidence: 99%
“…Iron levels in the brain are of central importance for neuronal function and survival. Increased levels of iron is considered to be responsible for the neurotoxic properties of Ldopa [8]. Iron-generated hydroxyl radicals are neurotoxic [9], and elevated iron levels are considered to play a role in the neurodegenerative mechanisms that underlie Alzheimer's and Parkinson's disease [10].…”
Section: Introductionmentioning
confidence: 99%